2016
DOI: 10.1016/j.ijrobp.2016.06.1985
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mode and Effects Analysis: A Community Practice Perspective

Abstract: lay solely with departmental leadership to follow-up on and address incidents. A few still expressed fear of retribution, describing being told not to document an incident by a co-worker. Other barriers such as time and accessibility were commonly described. Learning was often described as increased awareness, resulting from expanded communication, and less frequently from explicit teaching. Practice improvement was rarely perceived as learning. Conclusion: Overall, the opportunity to influence patient safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…23 For a general external beam process with support from a trained facilitator, total FMEA including analysis was estimated at 75 h. 15 Three centers exploring FMEA for radiosurgery identified 104-135 failure modes but completed the process over a period of 2-6 months. 10 The most extensive example of an FMEA might be that offered by Schuller et al 12 who identified a total of 409 failure modes, applied analysis to all modes and required an estimated total of 258 h, equivalent to 34 and a half working days. Variation and uncertainty in resource requirements could potentially act as a barrier to a center considering FMEA-based risk assessment for new or existing services and prevent more widespread practical implementation.…”
Section: D | Resource Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 For a general external beam process with support from a trained facilitator, total FMEA including analysis was estimated at 75 h. 15 Three centers exploring FMEA for radiosurgery identified 104-135 failure modes but completed the process over a period of 2-6 months. 10 The most extensive example of an FMEA might be that offered by Schuller et al 12 who identified a total of 409 failure modes, applied analysis to all modes and required an estimated total of 258 h, equivalent to 34 and a half working days. Variation and uncertainty in resource requirements could potentially act as a barrier to a center considering FMEA-based risk assessment for new or existing services and prevent more widespread practical implementation.…”
Section: D | Resource Implicationsmentioning
confidence: 99%
“…The resource requirements for conducting an FMEA are under reported in the literature with relatively few papers providing timings. 12,13,15,23 Reported timings range from 30 23 to 258 12 h, dependent on methodology. For a radiotherapy center considering adopting FMEA this information is particularly important, as there is cost associated with embarking on convoluted and lengthy risk assessments, particularly when considering an active service.…”
Section: E | Resource Requirements Of Fmeamentioning
confidence: 99%
See 1 more Smart Citation
“…What qualifies as high‐risk is highly arbitrary and is dependent on the number of risks involved in the process and their RPN scores. Some studies cite a lower threshold for high‐risk activities and classify all failure modes with RPNs greater than 100 or severity scores of 9 or 10 as high‐risk . However, as in Figure , if most failure modes lie above this RPN threshold, we suggest targeting the largest one or two RPNs calculated.…”
Section: What Is Fmea?mentioning
confidence: 99%
“…In this study, we apply the American Association of Physicists in Medicine (AAPM) Task Group 100 (TG-100) Failure Modes and Effects Analysis (FMEA) methodology 22 to apply modern risk-based analysis techniques to IGCSAI, as it has been done for a number of other medical physics applications. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] In the process, we propose a new process map specific to IGCSAI that changes the paradigm from individual errors in radiation delivery, to groups that are highlighted in a proposed new severity table. We also perform a preliminary FMEA survey based on expert opinion from SARRP operators.…”
Section: Introductionmentioning
confidence: 99%